Adolescents’ appraisal and disclosure mediate the links between parental practices and adolescents’ digital citizenship behaviors - Agustín Morales-Álvarez; Angel Alberto Valdés-Cuervo; Lizeth Guadalupe Parra-Pérez; Fernanda Inéz García-Vázquez; María Fernanda Durón-Ramos (Humanities & Social Sciences Communications)
Abstract Parenting-related factors are associated with adolescents’ online behaviors. However, the relationship between parenting and digital citizenship behaviors in adolescents and the variables underlying these relations must be clarified. This study examined the relationship between parental warmth, autonomy support, and provision of structure with digital citizenship behaviors. Additionally, whether adolescents’ appraisal of parental practices and media disclosure mediate these relationships. The study included 709 Mexican adolescents aged 11–18 (52% female) who completed self-report questionnaires. The analysis using latent structural equation modeling found that both parental warmth and autonomy support were positively associated with digital citizenship behaviors, while parental structure provision did not show a significant relationship. The study also revealed that adolescents’ positive appraisal of parental practices and media disclosure mediate the relationships between parental practices and digital citizenship behaviors separately and sequentially. These findings indicate that parental warmth, autonomy support, and structure provision may enhance digital citizenship behaviors in adolescents through positive appraisal of parenting and media disclosure.